STRENGTHENING SOCIAL ENGAGEMENT IN SUSTAINABLE DEVELOPMENT GOALS - Moh. Dulkiah (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2025)
This research examines social engagement in Sustainable Development Goals in rural areas of West Java Province, Indonesia, which aims to integrate sustainable development into strategies and policies at the community level. Even though the Sustainable Development Goals program has been running since 2015, citizen involvement and participation is still relatively minimal. The research method uses a qualitative approach by utilizing data collection techniques through field research in the form of observation, in-depth interviews and Focus Group Discussions with community leaders and related stakeholders. The main findings show that community groups play an active role in physical development and increase local capacity in resource management, with significant support for the sustainability of programs. The complexity of political, economic, cultural and social factors has influenced social engagement, as well as its implications for achieving sustainable development goals. This research contributes to an in-depth understanding of the role of communities in the context of rural development, with implications for implementing strategies and policy development that are more inclusive and sustainable in the long term.